Dinâmica demográfica do município de Santa Maria/RS: o estudo acerca das relações de conjugalidade através dos contextos do patriarcado e do espaço paradoxal - Caetano, Geani Nene (2013)
This dissertation aims to understand the demographic dynamics of the city of Santa Maria/RS through the focus on gender and conjugal relations. Thus, it intended to, as a main objective, understand the gender relations/relationships through the patriarchate and paradoxical space contexts, which are concepts of primal importance for Feminist Geography and Gender Studies. The research has the following specific objectives: a) to spatialize the analysis of demographic dynamics in Santa Maria/RS, focusing on the different values of the demographic data (finance, literacy, household heads, the proportion of population by sex gender), according to the 2010 census; b) to achieve interpretations for the correlations between census data on the quality and perception of women which live in the spatial area obtained in the goal "a" c) to interpret the population dynamics through the conjugal relations/relationships, considering the social conditions of women at Agroindustrial Street, spatial area of study. Methodologically, the research steps are grounded on interpretations offered by interviews with women that live in that neighborhood, in order to express their experiences. Among the study results, it emphasizes the maintenance of patriarchal conceptions in the interviewees‟ speech, even though most of them were already have inserted in the labor market and access to educational improvement.